Settlement Change Across Medieval Europe : Old Paradigms and New Vistas. - Brady, Niall (Ruralia Ser., 2019)
The idea that the past was an era with long periods of little or no change is almost certainly false. Change has always affected human society. Some of the catalysts for change were exogenous and lay in natural transformations, such as climate change or plant and animal diseases. Others came from endogamous processes, such as demographic change and the resulting alterations in demographic pressure. They might be produced by economic changes in the agrarian economy such as crop- or stock-breeding or better agricultural husbandry systems with the resultant greater harvests. Equally, they might b.